SYNTHETIC AUXINS AND AFtBUSCULAR MYCORRIZHAL FUNGI INTERACTION: INFLUENCE ON VEGETATIVE GROWTH OF SOUR ORANGE (Citrus aurantium L.) SEEDLINGS - DUTRA SOUZA, PAULO VITOR (1996)
Arbuscular mycorrhizae (Glomus intraradices Schenck & Smith) increased root and shoot growth, and P content in sour orange (Citrus aurantium L) seedlings. The application of indolebutyric acid (IBA) at 2.0 g/I as root dip was innefective in increasing growth to nonmycorrhizal seedlings, but applications to mycorrhizal seedlings had a positive interactive effect. The application of naphthaleneacetic acid (NAA) at 0.5 g/I was innefective to both nonmycorrhizal and mycorrhizal seedlings.